THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON TEACHER PERFORMANCE AT SMK PGRI 2 KEDIRI - Cendy Ariditya Mandagi; Aprilia Dian Evasari (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
Education is the most important thing that every individual must have. Educational service institutions such as Vocational High Schools require good management of students to achieve goals companies in the current era of globalization. This research aims to determine the influence of work discipline and work motivation on teacher performance at SMK PGRI 2 Kediri. The analysis techniques used are validity test, reliability test, classical assumptions, multiple linear regression analysis, coefficient of determination test, t test, F test. The population of this study was all 63 employees and a sample of 63 respondents because it used a saturated sample. The results of research at SMK PGRI 2 Kediri show that the work discipline variable (X1), and work motivation (X2) together they influence the performance variable (Y). Proven by the Fcount value of 244,417 > 3.15 Ftable.